Naturopathic Doctors: An Underutilized Resource of Whole Health Delivery in Primary Care - Adam Sadowski ND, MS; Luciano Garofalo ND, MS; Alanna Welsh ND, MS; Ryan Bradley ND, MPH (SAGE Publishing, 2022)
Naturopathy, recognized by the National Institutes of Health and the World Health Organization as a distinct system of complementary and integrative health care, is an existing model of whole health delivery. Its unifying principles, respect for the interconnectedness of biological systems, and representation globally uniquely positions naturopathy to serve an integral role in addressing the needs of primary health care. In this viewpoint, we aim to 1) highlight key areas and existing literature supporting the use of naturopathy for health promotion and disease prevention of noncommunicable diseases; 2) describe how naturopathy can addresses the mental health needs of today's societies; and 3) discuss the importance of naturopathy in the access and navigation of complementary and integrative health therapies.